2022
DOI: 10.1021/jacs.2c01214
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Three-Dimensional Perovskite Nanocrystals with Chiral-Induced Spin Selectivity for Room-Temperature Spin Light-Emitting Diodes

Abstract: We developed type-II core−shell nanocrystals (NCs) with a chiral low-dimensional perovskite shell and an achiral 3D MAPbBr 3 core. The core−shell NCs exhibit spin-polarized luminescence at the first excitation band of the achiral core, which is due to the chiral-induced spin selectivity (CISS) effect-governed spin-dependent shell-to-core electron transportation and the subsequent electron− hole recombination in the core. The preferred spin state of the transferred electrons is determined by the handness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 57 publications
0
73
0
Order By: Relevance
“…Subsequently, the concept has been extended to obtain chiral LHP NCs that exhibit CPL. , Chiral LHP NCs have received increasing attention, and a number of reports have been published over the years (Table ). In particular, numerous studies have been carried out inducing chirality in perovskite nanoplatelets (NPLs). , This is because the NPLs exhibit a higher surface-to-volume ratio that leads to a higher ligand density and, thus, they show a relatively high degree of chirality.…”
Section: Imparting Of New Functionalities By Ligandsmentioning
confidence: 99%
“…Subsequently, the concept has been extended to obtain chiral LHP NCs that exhibit CPL. , Chiral LHP NCs have received increasing attention, and a number of reports have been published over the years (Table ). In particular, numerous studies have been carried out inducing chirality in perovskite nanoplatelets (NPLs). , This is because the NPLs exhibit a higher surface-to-volume ratio that leads to a higher ligand density and, thus, they show a relatively high degree of chirality.…”
Section: Imparting Of New Functionalities By Ligandsmentioning
confidence: 99%
“…Xiong et al reported a series of metal-free three-dimensional (3D) perovskite ferroelectrics based on chiral organic cation templates, while Sargent et al studied spin-polarized absorption and photoluminescence from reduced-dimensional chiral perovskites . Our group developed second-order nonlinear optical (NLO) materials with high efficiency circularly polarized second-harmonic generation (SHG) based on chiral HOMH perovskites. ,, With that, chiral HOMHs have been booming as remarkable chiroptical materials owing to their exceptional chiroptoelectronic properties for broad applications in many emerging fields ranging from circularly polarized photodetectors and circularly polarized light-emitting diodes to spintronic devices . The strategies to synthesize such chiral HOMHs mainly involve the in situ synthesis based on chiral organic precursors and the ex situ synthesis by postfunctionalization with chiral ligands after the reaction. , However, these strategies are subject to the limited choices of chiral organic ligands, which greatly restrict the chemical diversity of chiral HOMHs.…”
Section: Introductionmentioning
confidence: 99%
“…Lead halide perovskites (LHPs) comprise a class of materials holding great promise for many optoelectronic applications. Due to the presence of lead and heavy halides, LHPs also exhibit a strong spin–orbital coupling (SOC) effect, , and this intrinsic feature triggers increasing efforts devoted to investigating and tuning the spin state in LHPs, as the strong SOC can allow for facile spin injection by using circularly polarized optical excitation. This property of LHPs, along with their low cost and solution processability, makes them a promising candidate for spin-related applications, such as quantum information science and spintronics. …”
mentioning
confidence: 99%